Medicinal activities of Tualang honey: a systematic review - Shamsol Azman, Ain Nabila Syahira; Tan, Jun Jie; Abdullah, Muhammad Nazrul Hakim; Bahari, Hasnah; Lim, Vuanghao; Yong, Yoke Keong (BioMed Central, 2024)
Natural products derived from various sources, including plants, have garnered significant interest as alternative therapeutic options. Among these, Tualang honey, extracted from the nectar of Tualang trees (Koompassia excelsa (Becc.) Taub.), has a long history of traditional use due to its therapeutic properties. This review aims to examine the pharmacological activities of Tualang honey, encompassing both in vitro and in vivo studies. A systematic search was conducted in multiple databases, including PubMed, Springer, Scopus, Wiley, and Science Direct, up until December 2022 to identify relevant studies on the pharmacological activities of Tualang honey. Two independent reviewers were involved in article selection, followed by data extraction and assessment of methodological quality using Syrcle's risk of bias tool. 123 articles were included, collectively describing the pharmacological activities of Tualang honey, including antimicrobial, anticancer, anti-inflammatory, antioxidant, antinociceptive, neuroprotective effects, and others. Tualang honey has significant promise as an alternative treatment option for treating a wide range of pathological diseases due to its wide range of pharmacological properties. Tualang honey's diverse array of pharmacological actions indicates its potential for multiple medicinal uses.